Impact of Training and Development on Employees’ Performance and Productivity - Ghalawat, Suman; Kiran,; Malik, Joginder Singh; Kumari, Neelam (Indian Journal of Extension Education, 2020)
The study was undertaken at DCM Textiles. The main purpose of this study was to check the impact of training and development on employees’ performance and productivity. Primary data was collected from 100 employees (working in morning, evening and night shift) of DCM Textiles, Hisar, through questionnaire. Questionnaire was divided into two parts; first part included demographic profiles whereas second part contained items relating to work feasibility, work environment, performance appraisal, organizational commitment cultural analysis, performance monitoring, employees’ satisfaction and improved productivity, personal factor and company ethics. Most of the respondents confirmed the important role of training and development on their performance and productivity. Factor analysis and Discriminant analysis showed that all the factors were contributing towards productivity and the variation in percentage were 12.359, 9.889, 8.990, 7.655, 7.228, 6.532, 6.005, 4.650 and 4.399 per cent respectively. As per factor analysis, factor1 to factor 9 were of most importance for the effective training, and the Cronbach alpha values were 0.691, 0.757, 0.705, 0.476, 0.616, 0.531, 0.409, 0.472 and 0.569, respectively. It can be concluded that working environment contribute the most followed by performance appraisal.
Keywords: Commitment; Ethics; Performance; Productivity; Variation; Work feasibility